Impact of corporate governance in restricting non-performing loans in commercial banks of Bangladesh - Ali, Sumaiya Tahsin (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.